Two new species of Indonemoura (Plecoptera: Nemouridae) from Fujian, China - Li, Weihai; Yang, Ding (Zootaxa, 2005)
Two new species of the family Nemouridae, Indonemoura fujianensis sp. n. and Indonemoura masuensis sp. n., are described from Fujian, South China. Their relationships with related species are discussed.